Materials experience : fundamentals of materials and design - Karana, Elvin; Pedgley, Owain; Rognoli, Valentina (Butterworth-Heinemann, 2014)
There currently exists an abundance of materials selection advice for designers, mostly suited to solving technical product requirements. In contrast, a stark gap can be found in current literature that articulates the very real personal, social, cultural and economic connections between materials and product design. In Materials Experience: Contemporary Issues Connecting Materials and Product Design, twenty four of the leading academicians and professional designers have come together for the first time to offer their expertise and insights on a number of topics common to materials and product design. The result is a very readable and varied panorama on the world of materials and product design as it currently stands. Contributions by many of the most prominent materials experts and designers in the field today, with a foreword by Mike Ashby. The book is organized into 4 main themes: sustainability, user interaction, technology and selection. Between chapters, you will find the results of interviews conducted with internationally known designers. These 'designer perspectives' will provide a 'time out' from the academic articles, with emphasis placed on fascinating insights, product examples and visuals.